Impact of Internet Banking Services on Customer Satisfaction: A Case Study of Bank Refah’s Customers, Northern Branches of Tehran - Majid Taghavipour (Journal of Global Pharma Technology, 2017)
This research has been conducted with the aim of investigating the effect of internet banking services on customer satisfaction, a case study of the northern branches of Tehran using the research model presented by Heba Khalil Asfour and Shafiq Haddad (2014), a model for admitting factors affecting mobile banking acceptance and its impact on increasing customer satisfaction. Based on this model, mobile bank components such as reliability, efficiency, accessibility, privacy, flexibility, ease of use and trust lead to customer satisfaction with mobile banking services. Therefore, given the same platform for mobile banking and internet bank as well as the same variables affecting both cases, and finally the optimal model used in this paper, this model was selected to measure the impact of the above mentioned variables on the satisfaction of internet bank customers. In this research, a sample of 384 clients of the Northern Branches of Tehran, Refah bank who used Internet Banking services was investigated using a descriptive-survey research method. Most samples were selected from the statistical population using a two-stage cluster method and according to the information obtained from the researcher-made questionnaire. Research findings indicated that all of the Internet banking components mentioned above has a significant impact on satisfaction of service users, but according to the results of the regression test, privacy has been identified as the most important factor.Keywords: E-banking, Customer satisfaction, Internet banking, E-commerce, Customer satisfaction.